Occurrence, Risks, and Treatment of Pharmaceutical Contaminants in Malaysia’s Aquatic Systems - Edita Ayoka Kiranparahita; Nur Afiqah Rahman; John Mwangi (Tecno Scientifica Publishing, 2026)
Pharmaceutical and personal care products (PPCPs) are increasingly recognized as emerging contaminants in aquatic ecosystems due to their persistence, bioaccumulation potential, and adverse effects on both human health and aquatic life. In Malaysia, particularly in the state of Selangor, the rapid growth in population and healthcare demand has led to rising pharmaceutical consumption and subsequent contamination of surface water, tap water, and drinking water sources. Recent studies have detected compounds such as diclofenac, triclosan, ciprofloxacin, caffeine, and sulfamethoxazole in local water bodies, with concentrations often exceeding those reported in developed countries such as Australia and Taiwan. This trend highlights the inefficiency of conventional wastewater treatment plants (WWTPs) in removing pharmaceutical residues. The persistence of these contaminants poses potential health risks, including antibiotic resistance, endocrine disruption, and long-term toxicity to aquatic organisms and humans. Current treatment technologies in Malaysia, including adsorption, bioremediation, and activated sludge systems, have shown partial removal efficiency but remain inadequate for complete elimination of PPCPs. To address this limitation, emerging research recommends integrating hybrid treatment systems that combine biological and physicochemical processes to enhance contaminant removal efficiency. The aim of this study is to assess the occurrence and distribution of pharmaceutical contaminants in Selangor’s aquatic system, evaluate their potential risks, and discuss the limitations of existing wastewater treatment technologies while proposing sustainable alternatives for improved water quality management. Overall, the findings emphasize the urgent need for policy revision, technological innovation, and stricter monitoring to safeguard public health and environmental integrity in Malaysia.